Utilization of safe male circumcision among adult men in a fishing community in rural Uganda - Lubogo, Mutaawe; Anguzu, Ronald; Wanzira, Humphrey; Shour, Abdul R.; Mukose, Aggrey D.; Nyabigambo, Agnes; Tumwesigye, Nazarius M. (African Health Sciences, 2019)
In Uganda, most-at-riskpopulations(MARPs) such as fishing communities remain vulnerable to preventable HIV acquisition. Safe Male Circumcision (SMC) has been incorporated into Uganda’s HIV prevention strategies. This study aimed at determining SMC utilization and associated factors among adult men in a rural fishing community in Uganda. A cross-sectional study was conducted in a rural fishing village in central Uganda. Stratified random sampling of 369 fishermen aged 18-54 yearswas used according to their occupational category; fish monger, boat crew and general merchandise.The dependent variable wasutilization of SMC.A forward fitting multivariable logistic regression model was fitted with variables significant at p≤0.05controlling for confounding and effect modification. Respondents’mean(SD) age was 30.0(9.3) years. Only8.4%hadSMC and among non-circumcised men, 84.9% had adequate knowledge of SMC benefits while 79.3% did not know were SMC services were offered.Peer support(AOR0.17;95%CI0.05-0.60) and perceived procedural safety (AOR6.8;95%CI2.16-21.17) were independently associated with SMC utilization. In this rural fishing community, SMC utilization was low. These findings underscore the need to inform HIV preventionstrategies inthecontextof peer support and perceptionsheld by rural dwelling men.
Keywords: Most-at-risk populations; Safe male circumcision; Utilization; Fishing community